Dinamika Interaksi Sosial Siswa dalam Perspektif Sistem Sosial di Sekolah - Yasin, Muhammad; Selfiana, Selfiana; Awie Mas’ud, Muhammad (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI SANGATTA Kab. Kutai Timur., 2024)
This research is based on the ethics of students in socializing in society which is less than optimal due to time constraints. Where, the time at school to learn and develop self-potential, religious spiritual abilities, self-control, personality, intelligence, noble character, and skills needed in himself and society is certainly less than optimal. Then from here, several questions arise regarding social dynamics in schools from a social system perspective and how to describe the analysis of social structures and interaction processes in the school context. This study aims to determine the relationship between students' social interactions at school and in the community as a social system that involves interactions between individuals who have different functions and roles, as well as various norms, values, and structures that regulate their behaviour. Then to elaborate on the analysis of social structures and social interaction processes in the school context, in this view, we will explore various aspects of social structures in the school context including hierarchical structures, classroom dynamics, relationships between students and teachers, as well as the roles of parents and administrative staff. The formal institution that is the object of this research is located at SMA Negeri 1 Sangatta Utara, East Kutai Regency. The research method that we conducted was a qualitative field method by collecting data as well as observations and interviews. From the research we conducted, it can be understood that school is an educational system that refers to social norms or values that need to be instilled in students in their practice to the community as well as the social structure and interaction process in school as a system emphasizing status, role, and power so that it will affect learning motivation and achievement.